FEMALE GENITAL MUTILATION AND ITS IMPLICATIONS - Agu, Benedicta N.; Agbaje, Olaoluwa S. (International Journal of Human Kinetics, Health and Education, 2023)
Female genital mutilation is one of the public health problems that is endangering the life and well-being of female in developing countries of the world. The paper reviewed the concept of FGM, defining it as cutting off part or whole of girl clitoris and some other part of her sex organ whether for cultural or any non-therapeutic reason. Reasons for female genital mutilation: FGM is practiced for cosmetic purposes; or as a sign of maturity. It may also be done to desensitize the clitoris thereby reducing libido and promiscuity, to prevent immorality, preparing female for marriage, increase cleanliness, to prevent labia hypertrophy, to improve fertility, to give more pleasure to the husband (by tightening the vagina), for religious rite and obligations. Specifically, this paper outlined the physical, psychological and social health (bioethical) implication of FGM as a public health problem. It has dangerous health implications because of the unsanitary conditions in which it is generally practiced. In addition, it is a fundamental violation of human rights because it is carried out at a very young age when there is no possibility of the individual consent and mutilated/cut infants, girls and women face irreversible lifelong health risks, among other consequences. Finally, measures for eradicating the practices of FGM were recommended, among which are capacity building of rural women through health education and advocacy.